Acceptance of coffee by different consumer profiles using multivariate statistics (Research, Society and Development, 2020)
This study aimed to evaluate the acceptance of coffee by consumers using olfactory sensory analysis in two moments: without and with information about the different classifications of the products. Three different coffee classifications (rio, hard, and soft) and a commercial sample of a Traditional type of coffee were used. The research was carried out in a supermarket in Lavras – MG - Brazil with 100 volunteers. Consumers were asked to evaluate the samples according to the 9-point hedonic scale without any prior information on coffee quality. Subsequently, the same test was applied after informing the consumers that there are differences in coffee quality (high, intermediate and low), which have different characteristics, including aroma. The most accepted samples were associated by consumers with coffees classified as hard and soft. The information provided about the differences in the quality of the samples influenced only females consumers with higher incomes.